Acute bulbar palsy as a variant of Guillain-Barré syndrome. (23rd February 2016) - Kim, Jong Kuk; Kim, Byung-Jo; Shin, Ha Young; Shin, Kyong Jin; Nam, Tai-Seung; Oh, Jeeyoung; Suh, Bum Chun; Yoon, Byeol-A; Park, Hwan Tae; Huh, So-Young; Oh, Seong-Il; Bae, Jong Seok
Abstract : Objective: To categorize a syndrome manifesting as prominent acute bulbar palsy (ABP) without limb motor weakness as a variant form of Guillain-Barré syndrome (GBS) and differentiate it from Miller Fisher syndrome (MFS) and pharyngeal-cervical-brachial (PCB) variants. Methods: We analyzed cases of ABP without limb motor weakness based on a dataset containing clinical information and the results of antiganglioside antibodies assays for acute immune-mediated neuropathies. Results: Eleven cases with an age at onset ranging from 18 to 65 years (mean 33.8 years) were identified as ABP-plus syndrome. All of the enrolled cases manifested with ABP as the predominant symptom, and with no limb weakness. The following features accompanied ABP in order of decreasing frequency: ophthalmoplegia (n = 9, 82%), ataxia (n = 9, 82%), and facial palsy (n = 6, 55%). An enzyme-linked immunosorbent assay study disclosed that immunoglobulin G (IgG) anti-GT1a antibodies were the most frequent (n = 11), followed by IgG anti-GQ1b antibodies (n = 6). Conclusions: We propose that ABP-plus syndrome without neck or limb weakness is a variant of GBS that is distinct from the MFS and PCB variants. The presence of IgG anti-GT1a antibodies can explain the relationships between the distinct clinical characteristics and the underlying pathomechanisms.